Persuasiveness of Statistics and Patients’ and Mothers’ Narratives in Human Papillomavirus Vaccine Recommendation Messages: A Randomized Controlled Study in Japan - Okuhara, Tsuyoshi; Ishikawa, Hirono; Okada, Masafumi; Kato, Mio; Kiuchi, Takahiro (Frontiers in Public Health, 2018)
Background The human papillomavirus (HPV) vaccination percentage among age-eligible girls in Japan is only in the single digits. This signals the need for effective vaccine communication tactics. This study aimed to examine the influence of statistical data and narrative HPV vaccination recommendation massages on recipients’ vaccination intentions. Methods This randomized controlled study covered 1,432 mothers who had daughters aged 12–16 years. It compared message persuasiveness among four conditions: statistical messages only; narrative messages of a patient who experienced cervical cancer, in addition to statistical messages; narrative messages of a mother whose daughter experienced cervical cancer, in addition to statistical messages; and a control. Vaccination intentions to have one’s daughter(s) receive the HPV vaccine before and after reading intervention materials were assessed. Statistical analysis was conducted using analysis of variance with Tukey’s test or Games–Howell post hoc test, and analysis of covariance with Bonferroni correction. Results Vaccination intentions after intervention in the three intervention conditions were higher than the control condition (p < 0.001). A mother’s narrative messages in addition to statistical messages increased HPV vaccination intention the most of all tested intervention conditions. A significant difference in the estimated means of intention with the covariate adjustment for baseline value (i.e., intention before intervention) was found between a mother’s narrative messages in addition to statistical messages and statistical messages only (p = 0.040). Discussion Mothers’ narrative messages may be persuasive when targeting mothers for promoting HPV vaccination. This may be because mothers can easily relate to and identify with communications from other mothers. However, for effective HPV vaccine communication, further studies are needed to understand more about persuasive differences in terms of statistics, narratives, and narrators. Directions for future research are also suggested.